MiR‐29a associates with viro‐immunological markers of HIV infection in treatment experienced patients. Issue 12 (6th June 2016) - Rosca, Adelina; Anton, Gabriela; Botezatu, Anca; Temereanca, Aura; Ene, Luminita; Achim, Cristian; Ruta, Simona
Abstract : MicroRNAs (miRNAs) are small, non‐coding RNA species essential for the post‐translational regulation of gene expression. Several miRNA have been proposed to contribute to Human immunodeficiency virus‐1 (HIV‐1) infection establishment, progression and latency. Among them, miR‐29a seems to be of particular interest. The aim of this study was to investigate the association between miR‐29a expression and immunologic and virologic markers of HIV infection progression in long‐term antiretroviral‐treated individuals. In a homogenous group of 165 young adults, with chronic HIV infection, parenterally acquired during childhood, the expression level of miR‐29a was found to be inversely correlated with HIV viral load and the degree of immunosuppression, expressed by both CD4 cell count and the CD4/CD8 ratio. There was a significant difference in miR‐29a expression according to the patient's response to treatment, with the lowest levels expressed by patients with treatment failure, defined as detectable viremia and CD4 < 350 cells/mm 3 . No significant correlation was found between miRNA level and the nadir CD4 count or zenith HIV viral load. This study establishes the association between miR‐29a expression and markers of HIV infection in long‐term survivors, treatment‐experienced patients, suggesting its potential use as an indicator for the on‐treatment disease evolution. J. Med. Virol. 88:2132–2137, 2016 . © 2016 Wiley Periodicals, Inc.